Errorless learning and spaced retrieval techniques to relearn instrumental activities of daily living in mild Alzheimer’s disease: A case report study - Stéphanie Thivierge (Dove Medical Press, 2008)
Stéphanie Thivierge1,2, Martine Simard1,2, Léonie Jean1,2, Éric Grandmaison31School of Psychology, Laval University, Quebec City, Quebec, Canada; 2Centre de Recherche Université Laval Robert-Giffard, Quebec City, Quebec, Canada; 3Neurosciences and Rehabilitation Units, Moncton Hospital, Moncton, NB, CanadaAbstract: Previous studies on cognitive training in Alzheimer’s disease (AD) were principally aimed at making patients learn items not related to functional needs. However, AD patients also experience difficulties with instrumental activities of daily living (IADL). The goal of the present multiple baseline case report study was to assess the preliminary efficacy and tolerability of an individualized cognitive training program using the errorless learning (EL) and spaced-retrieval (SR) techniques to relearn forgotten IADLs in mild AD. Following an exhaustive neuropsychological assessment, two participants received two training sessions per week during four weeks. Participant A was trained to use his voice mail and Participant B, to manage the messages from his answering machine. The results showed that the program was well tolerated and improved performance on the trained tasks. These ameliorations were maintained over a 5-week period. The effects of the training did not have any impact on global cognitive functions since the results on these measures remained relatively stable. This case report demonstrated preliminary efficacy of a new cognitive training program using EL and SR techniques tailored to the needs of AD patients. This is an important finding since the loss of these capacities alters autonomy in AD patients.Keywords: Alzheimer’s disease, errorless learning, spaced retrieval, memory, IADLs